Case Series: Abscopal Benefit of Surgery in 3 Immunotherapy-Treated Patients With Unresectable Cancer - Bryan Oronsky MD; Chris Larson MD, PhD; Tony R. Reid MD, PhD; Corey A. Carter MD (SAGE Publishing, 2018)
For all of the optimism that immunotherapy has engendered, the flip side is that 7/10 patients with susceptible tumor types do not respond, while in nonsusceptible tumor types the response rates are significantly lower. In contradiction of the current orthodoxy against surgery in the setting of unresectable disease, we present 3 examples of immunotherapy-treated patients with widespread recurrence who experienced dramatic clinical improvement following debulking/metastasectomy. Taken together with examples from the literature that correlate longer survival with surgical intervention during treatment with immunotherapy, these 3 cases suggest that a new paradigm involving a wider role for surgery in the management of these patients should be explored. Possible mechanisms by which surgery may synergize with immunotherapy and improve outcomes are also discussed.